Evaluation of Selected Properties of Dielectric Barrier Discharge Plasma Jet - Kwiatkowski, Michał; Terebun, Piotr; Kučerová, Katarína; Tarabová, Barbora; Kovalová, Zuzana; Lavrikova, Aleksandra; Machala, Zdenko; Hensel, Karol; Pawłat, Joanna (Materials (Basel, Switzerland), 2023)
In the technological processes requiring mild treatment, such as soft materials processing or medical applications, an important role is played by non-equilibrium plasma reactors with dielectric barrier discharge (DBD), that when generated in noble gases allows for the effective treatment of biological material at a low temperature. The aim of this study is to determine the operating parameters of an atmospheric pressure, radio-frequency DBD plasma jet reactor for the precise treatment of biological materials. The tested parameters were the shape of the discharge (its length and volume), current and voltage signals, as well as the power consumed by the reactor for various composition and flow rates of the working gas. To determine the applicability in medicine, the temperature, pH, concentrations of H2O2, NO2- and NO3- and Escherichia coli log reduction in the plasma treated liquids were determined. The obtained results show that for certain operating parameters, a narrow shape of plasma stream can generate significant amounts of H2O2, allowing for the mild decontamination of bacteria at a relatively low power of the system, safe for the treatment of biological materials.
Keywords: dielectric barrier discharge; plasma jet; atmospheric pressure plasma; biological materials; reactive oxygen and nitrogen species; Escherichia coli; plasma treatment of liquid